Queen's apprentice : archduchess Elizabeth, empress María, the Habsburgs, and the Holy Roman Empire, 1554-1569 - Patrouch, Joseph F., 1960- (Studies in medieval and Reformation traditions, 2010)
This study seeks to examine a number of themes relating to the roles of the women's court of the central European Habsburgs. These include its role in helping consolidate their holdings in central Europe and the Holy Roman Empire and structure their relations with the rest of Europe.